2007
DOI: 10.1590/s1415-47572007000100009
|View full text |Cite
|
Sign up to set email alerts
|

Genetic characterization of the Spanish Trotter horse breed using microsatellite markers

Abstract: To assist in selection schemes we carried out the first genetic characterization of the Spanish Trotter horse (Trotador Español). We used 16 microsatellite markers to genotype 40 unrelated Spanish trotters, 25 native Balearic horses (11 Menorquina and 14 Mallorquina horses) and 32 Andalusian horses. The observed heterozygosity for the Spanish Trotters was 0.647 ± 0.037 and the expected heterozygosity was 0.696 ± 0.026 while the average number of alleles per locus was 6.0 ± 0.341, these values being similar to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…Although several studies [2, 8, 9, 12] reported population studies on the genetic pedigree structure of several horse breeds, only limited information is available about data needed in casework such as the power of identity and breed assignment [4, 16]. In this study, allele M and Q of ASB23 marker, G of HMS2 marker, H and L of HTG6 marker, L of HTG7 marker, E of LEX3 marker confirmed as the specific alleles unique to Halla horses.…”
Section: Resultsmentioning
confidence: 99%
“…Although several studies [2, 8, 9, 12] reported population studies on the genetic pedigree structure of several horse breeds, only limited information is available about data needed in casework such as the power of identity and breed assignment [4, 16]. In this study, allele M and Q of ASB23 marker, G of HMS2 marker, H and L of HTG6 marker, L of HTG7 marker, E of LEX3 marker confirmed as the specific alleles unique to Halla horses.…”
Section: Resultsmentioning
confidence: 99%
“…The microsatellite markers analyzed were 17 loci (Table 1) recommended by the ISAG for equine parentage and identification testing (LEAR et al, 1999;DIMSOSKI, 2003;AZOR et al, 2007;VAN DE GOOR et al, 2010; EQUINE GENETICS AND PARENTAGE ANALYSIS WORKSHOP, 2012). Microsatellites were co amplified with the Equine Genotypes Panel 1.1 (Thermo Scientific), under conditions recommended by the manufacturer.…”
Section: Pcr Amplification and Capillary Electrophoresismentioning
confidence: 99%